2009
DOI: 10.1111/j.1469-8137.2009.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the culturable root bacterial endophyte community of Nicotiana attenuata is organized by soil composition and host plant ethylene production and perception

Abstract: Summary• A plant's bacterial endophyte community is thought to be recruited from the rhizosphere, but how this recruitment is influenced by the plant's phytohormone signaling is unknown. Ethylene regulates plant-microbe interactions; here, we assess the role of ethylene in the recruitment of culturable endophytic bacteria from native soils.• We grew wild-type Nicotiana attenuata plants and isogenic transformed plants deficient in ethylene biosynthesis (ir-aco1) or perception (35S-etr1) in four native soils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 62 publications
(120 reference statements)
4
77
0
Order By: Relevance
“…Germination procedures have been described elsewhere (Ryu et al, 2003;Long et al, 2010). The plant growth-promoting Bacillus sp B55 strain (GenBank accession number JX101913) was isolated from a 35S-etr1 plant grown in native Utah soil in 2008 (Long et al, 2010).…”
Section: Plant Materials and Bacterial Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Germination procedures have been described elsewhere (Ryu et al, 2003;Long et al, 2010). The plant growth-promoting Bacillus sp B55 strain (GenBank accession number JX101913) was isolated from a 35S-etr1 plant grown in native Utah soil in 2008 (Long et al, 2010).…”
Section: Plant Materials and Bacterial Strainmentioning
confidence: 99%
“…Recently, several studies have highlighted ET's prominent role in mediating mutualistic plant-microbe interactions (Penmetsa and Cook, 1997;Iniguez et al, 2005;Long et al, 2010) and due to its gaseous nature, studies on microbial VOC-mediated signaling processes in plants have focused on ET (Bailly and Weisskopf, 2012). Indeed, ethylene insensitive2 mutants are nonresponsive to VOC-mediated PGP by B. amyloliquefaciens IN937 and Piriformospora indica (Ryu et al, 2003;Camehl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than seed-borne bacteria, plants have also been known to recruit bacteria from the surrounding soil during germination. 33,34) Potato might have a different survival strategy from that of soybean in the early growth stage. Further study is needed to investigate this hypothesis.…”
Section: Soybeanmentioning
confidence: 99%
“…ET signaling influenced the endophytic bacterial communities in Nicotiana attenuate. It was observed that isogenic transformed plants impaired in ET biosynthesis (ir-aco1) or perception (35S-etr1) plants harbored culturable bacterial communities of a lower diversity than wild-type plants (Long et al, 2010). From the abovementioned studies, it seems that contrary to the studies on single bacterial isolates, the influence of the signaling pathways on endophytic bacterial communities are variable and may be small.…”
Section: Plant Hormone Signaling Pathways and Endophytic Bacterial Comentioning
confidence: 97%